2014
DOI: 10.1111/anae.12586
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of clinically symptomatic pneumothorax in ultrasound‐guided infraclavicular and supraclavicular brachial plexus block

Abstract: SummaryThe use of periclavicular brachial plexus block as regional anaesthesia for surgical procedures on the upper extremity is common. However, the proximity of the pleura results in a risk of pneumothorax. Without ultrasound monitoring, the pneumothorax risk has been reported to be as high as 6.1%. We conducted a prospective, observational study to examine the risk of pneumothorax in 6366 ultrasound-guided periclavicular plexus blocks. All patients with a clinically manifest and radiologically confirmed pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(30 citation statements)
references
References 55 publications
1
25
1
1
Order By: Relevance
“…We recommend further studies focusing in adverse effects of perineural injection of these drugs. We saw no immediate side effect in this study, but intravascular injection of local anesthetics and pneumothorax were reported in other studies (20, 21). …”
Section: Discussionsupporting
confidence: 58%
“…We recommend further studies focusing in adverse effects of perineural injection of these drugs. We saw no immediate side effect in this study, but intravascular injection of local anesthetics and pneumothorax were reported in other studies (20, 21). …”
Section: Discussionsupporting
confidence: 58%
“…The reported incidence of pneumothorax without ultrasound guidance ranges between 0.5-6% whereas with the aid of ultrasound guidance the incidence is 1%. 13,14,15 Other complications that may occur include injury to the recurrent laryngeal nerve resulting in a hoarse voice (a reported incidence of 1%), phrenic nerve injury resulting in hemidiaphragmatic paresis (a reported incidence of 33%), and vascular puncture (a reported incidence of 0.4%). 13,14,15 Horner's syndrome has also been described and results from paralysis of the ipsilateral sympathetic cervical chain caused by drugs, surgery or local compression (a reported incidence of 1%).…”
Section: Advantages Of Ultrasound-guided Supraclavicular Bp Blocksmentioning
confidence: 99%
“…13,14,15 Other complications that may occur include injury to the recurrent laryngeal nerve resulting in a hoarse voice (a reported incidence of 1%), phrenic nerve injury resulting in hemidiaphragmatic paresis (a reported incidence of 33%), and vascular puncture (a reported incidence of 0.4%). 13,14,15 Horner's syndrome has also been described and results from paralysis of the ipsilateral sympathetic cervical chain caused by drugs, surgery or local compression (a reported incidence of 1%). 13,14,15 The latter can be caused by the injection of large volumes of local anaesthetic or the atypical proximal migration of the solution above the clavicle toward the interscalene area.…”
Section: Advantages Of Ultrasound-guided Supraclavicular Bp Blocksmentioning
confidence: 99%
See 2 more Smart Citations